Imageability and Neighborhood Density Facilitate the Age of Word Acquisition in Czech - Smolík, Filip (Journal of speech, language, and hearing research, 2019)
Purpose The study examined the effects of imageability and phonological neighborhood density on the acquisition of word production in Czech, controlling for part-of-speech class, word length, and word frequency. Phonological neighborhood density is of interest because previous research has not examined highly inflected languages such as Czech. The effects of imageability on word acquisition are widely assumed, but only a few empirical studies examined such effects using child data directly. Method Data from the Czech norming study of the MacArthur-Bates Communicative Development Inventories ( Smolík, Turková, Marušincová, & Malechová, 2017 ) adaptation were used, and all nouns and action words in the data set were examined (total 359). Based on the norming sample of 493 children, the expected age of acquisition was calculated. Results A small but significant effect of neighborhood density (explaining 1.5% of unique variance) was found, as well as a robust effect of imageability (9% of unique variance). Imageability also accounted for the difference between nouns and verbs in the age of acquisition. Conclusion Imageability is a robust predictor of word age of acquisition that should be taken into account in future studies. The identifiability of the referent and the memory mechanisms are likely responsible for the strong imageability effect. Words with large phonological neighborhoods are acquired earlier, even in a language with complex inflectional morphology.
Keywords: Infant; předškolní dítě; Age Factors; Phonetics; Language Development; věkové faktory; lidé; Imagination; jazyk (prostředek komunikace); imaginace; Humans; kojenec; Czech Republic; Child, Preschool; vývoj řeči; Language; Česká republika; fonetika; Vocabulary; slovní zásoba